2019
DOI: 10.1002/ps.5328
|View full text |Cite
|
Sign up to set email alerts
|

Induced novel psbA mutation (Ala251 to Thr) in higher plants confers resistance to PSII inhibitor metribuzin in Lens culinaris

Abstract: BACKGROUND Weed competition is a major limitation to worldwide lentil (Lens culinaris Medik.) production in part due to limited effective safe herbicide options. Metribuzin is a photosystem II inhibiting herbicide that provides broad spectrum weed control, however it causes excessive injury in lentil. Dose response analysis of photosystem II inhibiting herbicides and DNA sequencing of the psbA chloroplast gene occurred to quantify the spectrum and mechanism of herbicide resistance in two ethyl‐methanesulfonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Chickpeas are sensitive to many postemergent herbicides registered for the control of broadleaf weeds in lentils or peas. The recent discovery of the Ala 251 Thr substitution in psbA chloroplast gene being responsible for resistance to a photosystem II inhibitor herbicide metribuzin (McMurray et al, 2019) has opened this a new avenue for creating herbicide resistance in chickpea and other legumes using gene editing. In another study, the identification and expression analysis of candidate genes involved in carotenoid biosynthesis in chickpea (Rezaei et al, 2016) has revealed several candidate genes as early knockout targets for improving carotenoid content in chickpea.…”
Section: Crispr/cas9 For Crop Improvement In Legumesmentioning
confidence: 99%
“…Chickpeas are sensitive to many postemergent herbicides registered for the control of broadleaf weeds in lentils or peas. The recent discovery of the Ala 251 Thr substitution in psbA chloroplast gene being responsible for resistance to a photosystem II inhibitor herbicide metribuzin (McMurray et al, 2019) has opened this a new avenue for creating herbicide resistance in chickpea and other legumes using gene editing. In another study, the identification and expression analysis of candidate genes involved in carotenoid biosynthesis in chickpea (Rezaei et al, 2016) has revealed several candidate genes as early knockout targets for improving carotenoid content in chickpea.…”
Section: Crispr/cas9 For Crop Improvement In Legumesmentioning
confidence: 99%